2018
DOI: 10.1158/1535-7163.mct-18-0399
|View full text |Cite
|
Sign up to set email alerts
|

ST8SIA1 Regulates Tumor Growth and Metastasis in TNBC by Activating the FAK–AKT–mTOR Signaling Pathway

Abstract: Breast cancer stem-like cells (BCSCs) are implicated in cancer recurrence and metastasis of triple negative breast cancer (TNBC). We have recently discovered that ganglioside GD2 expression defines BCSCs and that ST8SIA1 regulates GD2 expression and BCSC function. In this report, we show that ST8SIA1 is highly expressed in primary TNBC; its expression is positively correlated with the expression of several BCSC associated genes such as BCL11A, FOXC1, CXCR4, PDGFRβ, SOX2 and mutations in p53. CRISPR knockout of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 44 publications
1
67
0
Order By: Relevance
“…EZR-negative tumor cells also show the significant upregulation of CD109 , ID4 , ST8SIA1 , and NR4A1 genes. In breast cancer, CD109, ID4, and ST8SIA1 are involved in the maintenance of stem cell phenotype [ 44 , 45 , 46 ], whereas NR4A1 promotes TGF-β-induced EMT and invasion [ 47 ]. Besides, these genes are associated with RFS of breast cancer patients according to Kaplan–Meier plotter [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…EZR-negative tumor cells also show the significant upregulation of CD109 , ID4 , ST8SIA1 , and NR4A1 genes. In breast cancer, CD109, ID4, and ST8SIA1 are involved in the maintenance of stem cell phenotype [ 44 , 45 , 46 ], whereas NR4A1 promotes TGF-β-induced EMT and invasion [ 47 ]. Besides, these genes are associated with RFS of breast cancer patients according to Kaplan–Meier plotter [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proliferating, neural stem cells express both GD3 as well as measurable levels of GD2 [ 70 ]. Interaction of GD3 with the EGF receptor was found to allow neural stem cells to continue to proliferate [ 71 ] while studies of breast cancer stem-like cells indicated that activation of the FAK-AKT-ERK-mTOR signaling pathway by GD2 enhanced cell proliferation ( Table 3 ) [ 72 ]. These observations support the hypothesis that GD3 and GD2 contribute to the undifferentiated state of neural stem cells (NSCs) and in NB that GD2 contributes to the oncogenic properties.…”
Section: Gangliosides In Neuroblastomamentioning
confidence: 99%
“…Overexpression of GD2 in tumors may occur as a consequence of aberrant expression of GD2 biosynthetic enzymes. For example, ST8SIA1 regulated GD2 expression and breast CSC function [40,57]. Overexpression of ST8SIA1 in MDA‐MB‐231 breast cancer cells increased GD2 at the cell surface and enhanced proliferation of the cells.…”
Section: Biological Roles Of Gd2 In Cancermentioning
confidence: 99%